Análise das representações sociais de dengue nos comentários de participantes de redes sociais do Ministério da Saúde - Vargas, Priscila Victorelli Pires (2020)
Main goal: Analyze Social Representations (SR) of dengue from digital comments of participants of the Brazilian Ministry of Health (MH) fanpage. Methodology: Online documentary research with a qualitative approach. The collection period was from December 1, 2018 to March 31, 2019, after approval by CEP / UFSCar. The work was divided into 3 stages, according to the specific goals. Step 1: analyze the users' manifestations with the contents using “like”, “comment” and “share” options, by creating a plan on Microsoft Excel in order to collect data from Facebook, Instagram and Twitter websites. Step 2: Analyze the information spread by the Ministry of Health on dengue throughout the three social networks. For the analysis of the thematic content, data were collected from 132 contents published by the Ministry of Health on dengue in the 3 social networks already mentioned. Step 3: Analyze the comments on dengue from participants in the social networks of the MH. 433 digital comments were collected on Facebook (general profile and combating dengue). The information from steps 2 and 3 was transcribed in two different Microsoft Word files and data treated separately on the IRAMUTEQ software. We use CHD for lexical analysis and class construction. Results: Stage 1: The same publication of signs and symptoms of the disease was the most “liked” on both Facebook and Twitter profiles. On step 2, corpus originated three classes: "Fighting the mosquito at home", "Arboviroses and their similarities" and "Prevention actions of the Aedes aegypti vector". On step 3, the corpus was also divided into 3 classes: “The mosquito is the problem, but it is the other's fault”, “Dengue is horrible: it causes pain and can lead to death” and “Care for dengue patients ”. The classes of steps 2 and 3 were analyzed separately, qualitatively, through the technique of thematic content analysis, in order to identify which is the main idea / object disclosed by the Ministry of Health and which are the SR of individuals in relation to dengue. Discussion: The publications are repeated, both on the same platform (Facebook, “general” and “combating dengue” profile) and on other social networks. It is on the specific profile that users interact most with the posts, including giving them more visibility (“sharing”). The communication model used is the informational one, without the participation of the population and consequently they do not change practices. Publications focus on the adult mosquito and the expression “combat”, the most used word, limiting actions to eliminating the vector. The main idea on the Ministry of Health publications, is focused on general mosquito prevention care and it differs from the SR of digital profiles, because for them “the mosquito is the problem, but the fault is the other's. It's horrible, it causes pain and death and needs care. Therefore, other sources of information, interactions between individuals, as well as situations experienced by them, may be contributing to this. This social representation will lead attitudes and behaviors of this social group when facing the disease: an attitude of passivity, not feeling co-responsible for control, despite the fear of contracting the disease. Final considerations: We suggest the word control, as it expands actions for better life conditions and encourages popular participation. Despite the informational communication model, we emphasize the importance of Facebook “fighting dengue”, due to its ability to disseminate information. Only information does not change attitudes, but this, when read and shared by groups, can interfere with SR. The wide communication, of different information, can provide the construction of emancipatory social representations and not only the reification of the representations that already exist.